Physicochemical Properties Of Used Cooking Oil Purified Using Shallot (Allium Cepa L.) Pell Adsorbent - Baiq Fitri Rahmayanti; Yudin Citriadin; Sulistiyana Sulistiyana; Azlan Kamari; Ali Al-Mokaram (Journal of Science and Science Education, 2021)
Damage to used cooking oil is caused by hydrolysis and oxidation processes, these reactions are formed due to the use of oil many times. In terms of physical damage occurred in the smell and color (brown oil, cloudy to blackish), chemical changes in the form of acid numbers and peroxide numbers are quite high. This study aims to determine (1) there is an effect of variations in the mass of the onion peel adsorbent on the physical properties of used cooking oil; (2) there is an effect of mass variation of onion peel adsorbent on the physical properties of used cooking oil; and (3) physicochemical properties of used cooking oil purified according to SNI 3741:2013. The research method uses an experimental research type with a quantitative approach. The study design used a completely randomized design (CRD). The data analysis technique used One Way ANOVA. The test parameters include odor test, color test, acid number test and peroxide number test. The adsorption temperature was constant at 70°C for 30 minutes, the mass variations of the onion peel adsorbent were 0 g (without onion skin), 5 g, 10 g, 15 g, and 20 g in 100 ml of used cooking oil. The results of the study of physical properties (smell and color), variations of 5 gr, 10 gr 15 gr and 20 gr produced "normal" odors, while variations of 10 gr, 15 gr and 20 gr color produced "normal". Furthermore, the chemical properties showed a decrease in the acid number after the purification process, the largest variation in the decrease in the acid number was in the 20 gr treatment as much as 74.56%, the largest decrease in the peroxide value in the 20 gr treatment as much as 90.63%.